2013
DOI: 10.1177/000313481307900204
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Vertical Sleeve Gastrectomy for the Treatment of Pseudotumor Cerebri

Abstract: Brief Reports should be submitted online to www.editorialmanager.com/ amsurg. (See details online under ''Instructions for Authors''.) They should be no more than 4 double-spaced pages with no Abstract or sub-headings, with a maximum of four (4) references. If figures are included, they should be limited to two (2). The cost of printing color figures is the responsibility of the author.In general, authors of case reports should use the Brief Report format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Twelve primary studies [18][19][20][21][22][23][25][26][27][28]30,31 were included in the systematic review, accounting for a total of 39 participants, all of whom were diagnosed with IIH preoperatively. Of the 39 participants, 38 were female, and the average age of all participants was 32.5 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve primary studies [18][19][20][21][22][23][25][26][27][28]30,31 were included in the systematic review, accounting for a total of 39 participants, all of whom were diagnosed with IIH preoperatively. Of the 39 participants, 38 were female, and the average age of all participants was 32.5 years.…”
Section: Resultsmentioning
confidence: 99%
“…One limitation of this analysis is the lack of high-quality primary studies on the topic of bariatric surgery as a treatment for IIH. Although 12 primary studies were included, the majority 18,19,[21][22][23][25][26][27][28]31 were case reports and case series. Given that case studies are particularly prone to reporting bias, the effects of bariatric surgery in the treatment of IIH may have been overestimated in our results.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review of the literature on bariatric surgery for treatment of IIH has included 17 papers (6 series and 11 case reports) (15) . Fifty-four of the 67 IIH patients treated with bariatric surgery underwent gastric bypass, while LSG was performed in only 6 patients reported in 1 study (reference not found in Pubmed, abstract in IFSO 2013 congress) and 1 case report (15)(16) .…”
Section: Introductionmentioning
confidence: 99%